Participation and satisfaction in a bioecological program in Physical Education according to sex, age and educational need in a compensatory centre - Lamoneda Prieto, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2020)
The purpose of this study is to analyze the levels of participation and satisfaction in a Physical Education program following a bioecological model according to sex, age and educational need. A total of 136 students with an average age of 14.25 years (DT = 1.66) participated, all belonging to a public centre located in an area at risk of exclusion. The results revealed that the levels of participation did not depend on sex, age or educational need. The values of attentive participation and lack of attendance were not positive (55.3% participated and 45.6% were absent); however, relative participation was satisfactory (between 68 and 90%), as was enjoyment (89.8%) and value of the program for personal life (93.2%). It is suggested that educational compensation programs be rethought, giving prominence to Physical Education from a bioecological orientation.